Czy Mohyła może być dzisiaj jeszcze symbolem pojednania? - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2008)
The example of Mogila’a personal involvement in the cause of revival and reunification of Eastern Christianity in the Republic of Poland in the first half of the 17th century into one organism wins recognition among the supporters of the religious idea of unity. On the other hand, the methods that he used in the realization of his conception o f bringing the Churches together are an object of controversy among the Orthodox faithful. That is why today it is impossible to say univocally whether the Orthodox metropolitan can be a symbol of reconciliation.